Артрозуюча (артрозивна) деформація (загальні уявлення, побудова теорії та методолоґії її реалізації) - Снісаренко П.; Snisarenko P. (My University, 2009)
Книга писана на основі докторської дисертації автора. Описується особлива форма біомеханічного артрозу, що притаманна тільки та виключно захворюванням суглобів, зумовленим спадковою схильністю. Особлива концепція вносить суттєві зміни в уявлення про артрози, в діаґностично-лікувальний процес та проґнозні аспекти цього виду артрозу. Книга пропонується для артролоґів, ортопедів та викладачів кафедр, пов’язаних з артролоґією

The book is based on the author's doctoral dissertation. It describes a special form of biomechanical arthrosis, which is characteristic only and exclusively of joint diseases caused by hereditary predisposition. The special concept introduces significant changes in the understanding of arthrosis, in the diagnostic and treatment process and prognostic aspects of this type of arthrosis. The book is recommended for arthrologists, orthopedists and lecturers of departments related to arthrology
Arthrosis (arthrosis) deformity (general concepts, construction of the theory and methodology of its implementation)